Assessment: The "Wild Card" in Student Affairs. Issue 1 (1st January 2021) - Castillo-Montoya, Milagros
Abstract : Assessment is a core competency in student affairs, but scholars in the field of higher education and student affairs know little about how practitioners perceive and approach learning about assessment. In this study with 20 students in a student affairs master's program, I found they perceived assessment as the "wild card" and had trepidation about learning assessment. They also viewed it as meeting accountability obligations, securing careers, or improving student services. Participants' prior experiences also informed their assessment notions with implications for graduate socialization.